Surface-based morphometry of the cerebral cortex in cognitive impairments of varying severity in patients with age-related cerebral small vessel disease - Elena I. Kremneva; Larisa A. Dobrynina; Kamila V. Shamtieva; Victoria V. Trubitsyna; Zukhra S. Gadzhieva; Angelina G. Makarova; Maria M. Tsypushtanova; Marina V. Krotenkova (Digital Diagnostics)
BACKGROUND: Analysis of structural magnetic resonance images is essential to assessing the main substrate of cognitive impairment in sporadic age-related cerebral small vessel disease, accounting for up to 45% of all dementia cases. Variations in the results of magnetic resonance morphometry applied in cerebral small vessel disease require extensive studies and clinical correlation.